Manhaj Mutakallimin in Usul Fiqh: Theoretical Foundations for Contemporary Islamic Economic Ijtihad - Sari Damayanti; Mustofa Hasan; Dudang Gojali; Sri Dewi Anggadini (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This article aims to examine in depth the Manhaj Mutakallimin within Ushul Fiqh as a theoretical foundation for the development of contemporary Islamic economic ijtihad. The study arises from the awareness that global economic transformation requires an Islamic legal paradigm capable of addressing challenges of rationality, relevance, and public interest while maintaining its normative foundation. Using a qualitative approach through library research, this study explores the epistemological principles of the Manhaj Mutakallimin as articulated by key scholars such as al-Juwaini, al-Ghazali, and Fakhr al-Din al-Razi. The analysis focuses on its rational structure, deductive reasoning from the revealed sources, and theological orientation that positions reason as a partner to revelation in deriving legal rulings. The findings indicate that the Manhaj Mutakallimin provides a solid theoretical framework for the emergence of Islamic economic ijtihad grounded in maqā ṣ id al-syarī'ah, rationality, and social justice. This approach proves relevant in addressing modern economic issues such as Islamic fintech regulation, digital financial instruments, and problem-based fiscal policies. Thus, the Manhaj Mutakallimin not only represents a methodological legacy in Ushul Fiqh but also offers a foundational paradigm capable of integrating revelation, reason, and context in constructing a just and sustainable Islamic economic system. Keywords: Manhaj Mutakallimin, Ushul Fiqh, Ijtihad, Islamic Economics, Maqā ṣ id al-Syarī'ah